Strategic management for Griffith Laboratories (Phils.), Inc. - Bernate, Romeo L. (Animo Repository, 1999)
The term paper contains the Strategic Management Plan proposed for Griffith Laboratories Phils., Inc., (GLPI). The company is into Proposed Condiments and Premixes segment of the Food Processing Industry. Its market includes the fast food and food service industry, meat processing, and fish processing in the food processing in industry. The food processing industry consists of several segments from agricultural to marine products. As mentioned earlier, these segments, or strategic groups as Mr. Porter calls them, include meat processing, fish and other marine products processing, dairy processing, fruit processing and ect. As of 1994, NSO has listed a total of 1,879 establishments engaged in food manufacturing out of 10, 726 in the manufacturing sector. Fifty one firms in food manufacturing sector were into meat processing, 62 establishments were engaged in preserving and canning of fish and other marine products, 137 went into bread and pastries segment, and 21 companies engaged into processed condiments and premixes. The rest belongs to other segments such as dairy processing, fruit and crops processing, and the like. In 1993, the fast food and food service industry the market of processed condiments and premixes, had a net sales of P11 billion. And in 1994, the net sales was close to P15 billion. Before the economic crisis that started in July 1997, the industry was estimated to grow annually by 25-30 percent. According to PDCP Bank Industry Study in 1994, the industry has been growing by 30% in the last 10 years. Today, the fasr food and food service market is close to 30 billion pesos. In 1996, the meat processing posted a gross revenue of P28.53 billion, the fish processing had P8.2 billion, and Bakery and pastries had P3.89 billion. With regard to macroeconomic situation, the Philippines economic condition beginning in the middle of 1997, being one of the countries that was hit by the currency crisis, is not in good shape relative to past years performances particularly in 1995 and 1996. As of November 1998, the GNP was recorded at 0.5 % and estimated to register at 1% maximum by the end of December this year. Despite this performance, NEDA is still optimistic to forecast a growth in GNP and GDP of 3.5 5.1 percent and 3.0 -4.5 percent respectively for the years 1999 – 2004. The inflation rate forecast for the same period is placed at 7.75 percent, although it reached a high of 11.5 percent towards the end of 1998. The foreign exchange rate is likewise expected to weaken against the U.S. dollar at an average rate of 5 percent per year. Technological development has greatly influenced the social condition in the country. High-tech gadgets, transportation, appliances, machines, and equipment have changed the peoples lifestyles, demographics, and social values. Income levels increased by more than 50 percent in 1997 compared to only 49 percent in 1991. Personal expandable income grew an average of 16.14 percent over the period of five years from 1988 to 1992. With regard to food expenditure pattern from 1991-1997, 47.7 percent of the total family income goes to food, of which 4.2 percent is on food consumed outside the home. Along with the technological advancement, the supply and demand pattern from consumable items to durable goods in shifting worldwide. As this developed, WTO, GATT, AFTA, and several others came into being to address the trend of globalization and e-commerce. The food processing industry in the Philippines has been growing positively despite the negative growth performance experienced by the whole manufacturing sector since the second half of 1997 up to August of 1998. Because of its stability relative to other sectors, the industry has been the object of potential entrants. The district taste and palatability of the industry products are not most likely threatened by home-made food as their substitute. Aside from direct consumers, the big industry buyers are companies themselves within and outside the food processing industry. Raw materials are supplied locally but the bulk of core ingredients are sourced from abroad. Using the framework of forces driving industry competition by Michael Porter, the overall intensity of rivalry in the food processing industry is low. This conclusion was influenced by differentiation and brand loyalty for the products. However, the threat of potential entrants is high since new investors do not contend with economies of scale, big initial capital requirement, and access to distribution channel. The presence of product differentiation and product loyalty made the bargaining power of the buyers low. On the other hand, because of homogeneity of raw materials supply and availability of different sources had likewise made the bargaining power of supplier low.